Soil heterogeneity modulates pollutant–nutrient coupled microbial cross-kingdom interactions and PAH-degradation in long-term contaminated industrial soils - Jianfeng Liu; Xinliang Hu; Huili Zhao; Chengbo Zhang; Liuqing Yang; Conghui Zhang; Yuchuan Fan; Yongping Shan; Bin Liu; Wentao Jiao (Journal of Environmental Chemical Engineering, 2026)

The preparation technology and catalytic mechanism of PVDF/PVP/a-MoSx porous membrane for water flow driven piezoelectric PMS activation - Yue Li; Conghui Wang; Minghao Fan; Xiang Yu; Gang Qin; Lele Qiu; Kai Yin; Longlu Wang (Chemical Engineering Journal, 2024)

A new method for creating androgenetic diploid fish from tetraploid carp sperm and their genetic composition analysis - Haoran Gu; Qilong Liu; Yi Fan; Qiong Liu; Yating Zhu; Conghui Yang; Shi Wang; Shaojun Liu (Aquaculture, 2024)

Amorphous molybdenum sulfide nanosheets composed of [Mo3S13]2- active-site motifs for enhancing conversion of Fe3+/Fe2+ in Fenton reaction under neutral condition - Yue Li; Minghao Fan; Bo Yu; Conghui Wang; Xiang Yu; Jun Ding; Gang Qin; Lei Yan; Kai Yin; Longlu Wang (Chemical Engineering Journal, 2024)

Coordination environment engineering of MoS2-based nanocomposite by Ni atom incorporation for enhanced peroxymonosulfate activation - Minghao Fan; Conghui Wang; Xiang Yu; Jun Ding; Lei Yan; Gang Qin; Yue Li; Longlu Wang (Chemical Engineering Journal, 2024)

Controllable growth of silver nanoparticles on titanium dioxide/nitrogen-doped carbon nanofiber/molybdenum disulfide: Toward enhanced photocatalytic-activating peroxymonosulfate performance and “memory catalysis” - Conghui Wang; Yue Li; Minghao Fan; Xiang Yu; Jun Ding; Lei Yan; Gang Qin; Jia Yang; Yongcai Zhang (Chemical Engineering Journal, 2024)

Insight into the role of SO2 on selenium conversion during adsorption by CaO: Theoretical calculation and experimental study - Mengzhu Yu; Fumitake Takahashi; Yaji Huang; Zihong Li; Hao Xu; Pu Yang; Zhicheng Zhu; Lu Dong; Conghui Fan; Kunio Yoshikawa (Journal of Hazardous Materials, 2023)

Transcriptome-wide identification of microRNAs in the roots of Pinus massoniana seedlings under Pi stress and Pi recovery - Zijing Zhou; Xianwen Shang; Fuhua Fan; Conghui Wang; Huijuan Qin; Jianhui Tan; Guijie Ding (Acta Physiologiae Plantarum, 2022)

Gully head activity and its influencing factors in China’s Loess Plateau - Jiaxi Wang; Conghui Fan; Yan Zhang; Zhen Li (Journal of Soils and Sediments, 2022)

Spatial correlations of daily precipitation over mainland China - Conghui Fan; Shuiqing Yin; Deliang Chen (International Journal of Climatology, 2021)
Knowledge of spatial correlations of precipitation is important for the generation of grid‐based surface precipitation data sets, deployment of data collection, selection of downscaling strategies, and interpretation of paleoclimate reconstructions. Spatial correlations of daily precipitation in China were analyzed based on a daily precipitation data set from 1951 through 2014 for 2,208 stations by dividing them into 13 regions. Interstation Pearson correlation coefficient r for the daily precipitation series and the corresponding interstation distance d were calculated for each region. The exponential spatial correlation model () was fitted by the r‐d pairs, in which c 0 , d 0 and s 0 were the parameter variance, scale and shape, respectively. The results showed that: (a) The determination coefficient R 2 of the correlation model varied from 0.54 to 0.96, with a mean of 0.82 and the regional maximum correlation distance d 0 varied from 102.2 to 201.7 km, with a mean of 155.2 km. Western regions generally had smaller d 0 than eastern regions, which indicates rain events in the western regions were more local; (b) The goodness‐of‐fit of the model was improved by dividing samples into West‐East (W‐E) and North‐South (N‐S) directions. The average of d 0 for all regions (190.2 km) for the W‐E direction is larger than that for the N‐S direction (142.9 km); (c) The correlation distances in summer and dry years are shorter than those in winter and wet years. However, the difference of correlation distance between dry and wet years was subtle compared with those between summer and winter, and between W‐E and N‐S directions. Seven regions were divided based on the spatial correlations of daily precipitation and different spatial models were suggested to be used for different regions, seasons and directions when the interpolation of daily precipitation is conducted for the generation of gridded surface precipitation data sets.

Sequences analyses and expression profiles in tissues and embryos of Japanese flounder (Paralichthys olivaceus) PRDM1 - Conghui Liu; Wei Liu; Lin Fan; Jinxiang Liu; Peizhen Li; Wei Zhang; Jinning Gao; Zan Li; Quanqi Zhang; Xubo Wang (Fish Physiology and Biochemistry, 2016)

Application of the Hilbert–Huang Transform to the Estimation of Air-Sea Turbulent Fluxes - Juanjuan Wang; Jinbao Song; Yansong Huang; Conghui Fan (Boundary-Layer Meteorology, 2013)

On the parameterization of drag coefficient over sea surface - Juanjuan Wang; Jinbao Song; Yansong Huang; Conghui Fan (Acta Oceanologica Sinica, 2013)

Amotion correction on direct estimations of air-sea fluxes froma buoy - Yansong Huang; Jinbao Song; Conghui Fan (Acta Oceanologica Sinica, 2013)

Air-sea carbon-dioxide flux estimated by eddy covariance method from a buoy observation - Yansong Huang; Jinbao Song; Juanjuan Wang; Conghui Fan (Acta Oceanologica Sinica, 2012)

Anti-tumor Function of Double-promoter Regulated Adenovirus Carrying SEA Gene, in the Treatment of Bladder Cancer - Jianpeng Hu; Xujun Xuan; Conghui Han; Lin Hao; Peiying Zhang; Meng Chen; Houguang He; Tao Fan; Binzheng Dong (Cell Biochemistry and Biophysics, 2012)

Mechanism of Monoclonal Antibody-Coupled Staphylococcus Superantigen-A Induced Apoptosis in Human Bladder Cancer Cells - Conghui Han; Zhen Gong; Lin Hao; Jianjun Yang; Jianpeng Hu; Bingzheng Dong; Tao Fan; Wenhao Tang; Gaojun Teng (Cell Biochemistry and Biophysics, 2011)